Analisis Kesalahan Siswa Dalam Pemecahan Masalah Matematika Pada Materi Peluang Berdasarkan High Order Thinking Dan Pemberian Scaffolding - Komarudin Komarudin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
This research is to analyze the students' difficulties in the problem-solving process. Based on the analysis, the mistakes made by the students in solving the mathematical problems of opportunity materials based on Polya step resulted in 100% understanding of the problem, drawing up the plan 81%, implementing the 81% plan and re-checking the solution by 100%. The type of mistakes most often done by students in doing problem solving problems mathematics of opportunity material, among others, in the process of understanding the problem of the error in determining what is known and asked, in the process of preparing a plan that is not write down the steps used in solving problems and students write down the steps used in solving the problem but not in accordance with the problem, the error in implementing the plan that is not write the formula used, the error in determining the conclusion that is not write the conclusion given, error in re-examine the solution is not doing the calculation when re-checking the solution. Scaffolding activities include environmental provisions 25%, explaining 25%, restructuring 17%, reviewing 17%, developing conceptual thinking 16%. This activity can improve students' problem-solving abilities on opportunity materials. It can be seen from the test results of both students who showed improvement and positive response of students after scaffolding activities. So it can be concluded that the scaffolding activities undertaken can have a positive impact on the students.